Successful Treatment of Post Kala-azar Dermal Leishmaniasis and Disseminated Tuberculosis Co-infection With Liposomal Amphotericin B and Anti-tubercular Drugs in Bangladesh. Issue 5 (September 2017) - Rashid, Md. Mahbubur; Nath, Proggananda; Rahman, Mizanur; Mondal, Dinesh; Shamsuzzaman, Abul Khair Mohammad; Basher, Ariful
Abstract : Abstract: We report a case of a 40-year-old male patient residing in a hyperendemic area of Bangladesh. The patient was diagnosed with disseminated tuberculosis and post kala-azar dermal leishmaniasis at Surya Kanta Kala-azar Research Centre. He had thickening, furrowing, and hyperpigmentation of the skin over both lower limbs and had nodular lesions on the face and earlobes and macular lesion on the back of the chest and limbs with intact sensation. Right-sided moderate pleural effusion, mild ascites, and mild hepatosplenomegaly were also found. He had positive result of Xpert MTB/RIF test from pleural fluid and tuberculin skin test. The results of rapid diagnostic test rK39, slit skin smear microscopy for Leishman-Donovan bodies, and polymerase chain reaction for skin sample of post kala-azar dermal leishmaniasis were found positive. Liposomal amphotericin B and anti-tubercular (Category 1) drugs were used simultaneously without any serious adverse effect, and improvement was found at a follow-up visit after 6 months of the treatment. Abstract : This report presents a case of post-kala-azar dermal leishmaniasis with extensive nodular lesions and disseminated tuberculosis that was treated successfully with three cycles of liposomal amphotericin B along with CAT-1 anti-tubercular drugs successfully without any adverse effects.